2019
DOI: 10.1111/cns.13199
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin attenuates early brain injury through regulating autophagy‐apoptosis interaction after subarachnoid hemorrhage in rats

Abstract: Aim To determine the effect of osteopontin (OPN) on autophagy and autophagy‐apoptosis interactions after SAH. Methods The endovascular perforation model of SAH or sham surgery was performed in a total of 86 Sprague‐Dawley male rats. The temporal expressions of endogenous OPN and autophagy‐related proteins (Beclin 1, ATG5, LC3 II to I ratio) were measured in sham and SAH rats at different time points (3, 6, 12, 24, and 72 hours). Rats were randomly divided into three groups: Sham, SAH + Vehicle (PBS, phosphate‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 41 publications
(85 reference statements)
0
32
0
Order By: Relevance
“…Apoptosis is triggered if p62-mediated autophagy is prohibited (Goodall et al, 2016). Cheng et al suggested that the neuronal apoptosis was inhibited by recombinant OPN via enhancing autophagy in subarachnoid hemorrhage-induced brain injury (Sun et al, 2019). Moreover, previous studies also proved that autophagy induction alleviated apoptosis in Parkinson's disease (Lin et al, 2014) and stroke (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is triggered if p62-mediated autophagy is prohibited (Goodall et al, 2016). Cheng et al suggested that the neuronal apoptosis was inhibited by recombinant OPN via enhancing autophagy in subarachnoid hemorrhage-induced brain injury (Sun et al, 2019). Moreover, previous studies also proved that autophagy induction alleviated apoptosis in Parkinson's disease (Lin et al, 2014) and stroke (Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…OPN is a neuroprotective glycoprotein expressed in various types of cells. Our previous studies showed that endogenous OPN expression increased after SAH induction [21,35]. Moreover, exogenous OPN treatment showed protective effects against vasospasm and blood-brain barrier disruption after SAH through integrin receptor-dependent activation of MKP-1 and MAPK phosphatase in astrocytes and endothelial cells [18,36].…”
Section: Discussionmentioning
confidence: 99%
“…Vehicle or rOPN was delivered via the nasal route 1 h after SAH induction, and brain samples were collected 24 h after SAH. The intranasal rOPN dosage was selected based on previous studies [7,21].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations